Nursing of an elderly long-term bedridden patient with purple urine bag syndrome (1例高龄长期卧床男性患者并发紫色尿袋综合征的护理体会) - MIAO Miao (苗苗); LI Jun (李君); YAN Tong (闫彤); SUN Yinan (孙依楠) (Journal of International Translational Medicine Limited, 2024)
This paper summarized the nursing management of an elderly long-term bedridden patient with purple urine bag syndrome. Given the association between purple urine bag syndrome and urinary tract infection, nurses had enhanced the interventions on catheter maintenance and urinary tract infection prevention. Meanwhile, comprehensive nursing interventions including diet guidance, constipation prevention and psychological care were carried out to relieve the clinical symptoms and negative emotions, and improve treatment adherence and recovery of the patient. (本文总结 1例高龄长期卧床男性患者并发紫色尿袋综合征(PUBS)的护理经验。PUBS的发生与尿路感染有关, 护理人员应加强导管维护和相关尿路感染护理, 同时给予饮食指导、便秘管理和心理护理, 改善患者便秘症状, 缓解负性情绪, 提高治疗依从性, 加快患者康复。)